Evaluation on the stability of expressway embankment combined with L-shaped thermosyphons and insulation boards in warm and ice-rich permafrost regions. (September 2021) - Luo, Xiaoxiao; Yu, Qihao; Ma, Qinguo; You, Yanhui; Wang, Jinchang; Wang, Shi
Highlights: The heat and deformation behaviors of a composite embankment are investigated. The formation mechanism of the cracks formed on the composite embankment is discussed. Some methods are proposed to alleviate the cracks for the composite embankment. The cooling and anti-instability effect of the composite measure are evaluated. Abstract: The embankment construction in permafrost regions changes the energy balance on the surface, resulting in the degradation of the underlying permafrost and instability in the embankment structure. Considering the strict evenness requirement for an expressway, large deformation and instability in expressway embankment cannot be allowed. Accordingly, in this study, a composite measure combined with two-phase closed thermosyphons (TPCTs) and insulation boards is proposed for stabilizing embankments. Moreover, a full-scale experimental expressway embankment is constructed in the Qinghai–Tibet Plateau (QTP) to analyze and investigate the stability of the composite embankment. The experimental results show that the composite measure significantly cools the permafrost under the embankment center and shady slope, and reliably alleviates the embankment deformation and deformation difference. However, the special ground temperature distribution around the TPCTs causes the asymmetric thermal regime and longitudinal cracks in the composite embankment. Additional reinforcement measures should be developed to alleviate the asymmetric thermal regime and prevent such longitudinal cracks. Moreover, timely repair of existing cracks and taking waterproofing measures in advance are favorable for embankment stability.